Conceptual Review of Ai-Enabled Human Resource Management (Hrm) Systems in Strategic Contexts (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The integration of Artificial Intelligence (AI) into Human Resource Management (HRM) represents a paradigm shift in organizational strategic planning and workforce management. This conceptual review examines the transformative role of AI-enabled HRM systems in strategic contexts, synthesizing current literature on implementation frameworks, organizational performance impacts, and emerging challenges.Through systematic analysis of recent empirical studies and theoretical frameworks, this paper explores how AI technologies including machine learning, predictive analytics, and natural language processing are revolutionizing core HR functions such as recruitment, performance management, talent development, and workforce planning. The review identifies significant positive relationships between AI-driven HRM practices and strategic organizational outcomes, including enhanced decision-making efficiency, improved employee engagement, and sustainable competitive advantage. However, critical challenges persist, encompassing algorithmic bias, ethical considerations, organizational readiness deficits, and employee resistance to technological change.The findings reveal that successful AI-HRM integration requires strategic alignment with organizational objectives, robust technological infrastructure, comprehensive change management protocols, and cultivation of AI literacy among HR professionals. This paper contributes to the evolving discourse on digital transformation in HRM by proposing a conceptual framework that integrates technological capabilities with human-centered design principles, emphasizing the necessity of balancing automation with ethical governance. Future research directions are identified, including longitudinal studies on AI-HRM impact sustainability, cross-cultural implementation variations, and the development of standardized ethical frameworks for AI deployment in human capital management.